A STUDY OF THE CONCEPT OF “HAYO-IBO” IN TRANSLATION FROM UZBEK TO ENGLISH: A STUDY OF THE CONCEPT OF “HAYO-IBO” IN TRANSLATION FROM UZBEK TO ENGLISH - Tursunboyeva, Munavvara (Журнал иностранных языков и лингвистики, 2021)
A STUDY OF THE CONCEPT OF “HAYO-IBO” IN TRANSLATION FROM UZBEK TO ENGLISH